Hubungan Obesitas Dengan Hipertensi Di Wilayah Kerja Puskesmas Mandala Medan Tembung Tahun 2023 - Dearmaita Purba, Sri; Frida Liharris Saragih (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Hypertension is also known as "the silent killer" because hypertension sufferers often go for years without experiencing any disturbances or symptoms and thus experience complications in vital organs. Hypertension is still a public health problem today because its prevalence is increasing. The aim of this research is to analyze the relationship between obesity and the incidence of hypertension at the Medan Tembung Mandala Health Center in 2023. The type of research used is analytical descriptive with a cross sectional study approach. The sample in this study was 92 people according to the inclusion and exclusion criteria using a purposive sampling technique. Data processing in this research is processed by cleaning, editing, coding and data entry. Data processing and data analysis were carried out using univariate analysis to describe the characteristics of the frequency distribution of respondents, and bivariate analysis using the chi-square test. The research results show that the P-value is 0.002, meaning there is a significant relationship between obesity and hypertension, and it is known that OR = 3.974, which means that people who are obese are 3.9 times more likely to suffer from hypertension compared to people who are not obese. It is recommended that patients need to maintain their diet, namely by reducing junk food and consumption of high sugar and high cholesterol foods, patients also need to understand about hypertension so they can make further prevention efforts, namely preventing heart failure complications.